2021
DOI: 10.1186/s12903-021-01660-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life in patients infected with HIV, Iran: a cross-sectional study

Abstract: Background The life expectancy of patients with Human Immunodeficiency Virus (HIV) has increased, but its oral manifestations can affect the Oral Health-Related Quality of Life (OHRQoL) of these patients. This study aimed to evaluate OHRQoL in HIV-infected patients and determine its related factors. Methods In this cross-sectional study, 250 HIV-infected patients were randomly selected from Shiraz Voluntary Counseling and Testing center in 2019. OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The same situation was shown in a study from Iran in 2019 [ 36 ], which found that although the life expectancy of PLWHA has increased, oral manifestations can affect the oral-health-related quality of life (OHRQoL) of these patients. PLWHA were worried about their dental health problems.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The same situation was shown in a study from Iran in 2019 [ 36 ], which found that although the life expectancy of PLWHA has increased, oral manifestations can affect the oral-health-related quality of life (OHRQoL) of these patients. PLWHA were worried about their dental health problems.…”
Section: Discussionsupporting
confidence: 64%
“…In a univariate analysis, the OHRQoL was significantly associated with the patient’s age ( p = 0.012), duration of the disease ( p = 0.009), job ( p = 0.006), edentulous status ( p = 0.003), and whether or not they wore dentures ( p < 0.001). However, in a multiple linear regression analysis, a significant difference was found only between denture-wearing and non-denture-wearing patients ( p ≤ 0.001) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those oral diseases negatively affect patients' OHRQoL and well-being. Oral conditions affect OHRQoL through interference with daily activities such as chewing, swallowing, speaking, sleeping, choosing what to eat, schooling social interaction, and more [3].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) distinguishes the Oral Health Related Quality of Life (OHRQoL) concept as essential to general and oral health. Also, WHO recognizes oral health as a signi cant part of the Global Oral Health Program [3]. For years, the impact of oral diseases on quality of life was ignored, and more effort was put into evaluating oral diseases clinically [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation